Clinical characteristics and risk factors for in-hospital mortality of COVID-19 patients in Hubei Province: A multicenter retrospective study - Wu He; Gen Li; Ke Xu; Bo Yu; Yang Sun; Kaineng Zhong; Da Zhou; Yongcui Yan; Junfang Wu; Dao Wen Wang (International Journal of Cardiology: Heart & Vasculature)
Background: Coronavirus disease (COVID-19) remains one of the most significant factors threatening public health security worldwide. The COVID-19 pandemic has been ongoing for more than 3 years; however, there are few studies on the clinical characteristics and mortality risk factors in patients with COVID-19 based on comprehensive data from multiple centers. Methods: A total of 53,030 patients with confirmed COVID-19 from 138 hospitals in Hubei Province were included in this study. We compared the clinical characteristics between survivors and non-survivors and analyzed the risk factors for in-hospital mortality. Results: Among the 53,030 patients with COVID-19, 49,320 (93.0 %) were discharged, and 3,710 (7.0 %) died during hospitalization. Cardiovascular disease was the most common comorbidity, followed by endocrine and digestive diseases. Male sex, >65-year-old, and high diastolic blood pressure, a series of abnormal laboratory test indicators and hyponatremia, hypokalemia, acute respiratory distress syndrome, shock, solid tumor, hematological tumor, and insulin use were independent risk factors for in-hospital mortality of patients with COVID-19. In addition, male sex, older age, and higher disease severity were associated with increased mortality in patients with COVID-19. Conclusion: Patients with early COVID-19 in Hubei Province had high mortality and a high proportion of severe cases and initial comorbidities. Cardiovascular disease was the most common comorbidity in patients with COVID-19. Male sex, older age, comorbidities, and abnormal laboratory data have been identified as independent risk factors for in-hospital mortality in patients with COVID-19. Therefore, there should be an increased focus on patients with COVID-19 with these risk factors.